2015
DOI: 10.1007/s13131-015-0738-0
|View full text |Cite
|
Sign up to set email alerts
|

The seasonal variations in the significant wave height and sea surface wind speed of the China’s seas

Abstract: Long-term variations in a sea surface wind speed (WS) and a significant wave height (SWH) are associated with the global climate change, the prevention and mitigation of natural disasters, and an ocean resource exploitation, and other activities. The seasonal characteristics of the long-term trends in China's seas WS and SWH are determined based on 24 a (1988-2011) cross-calibrated, multi-platform (CCMP) wind data and 24 a hindcast wave data obtained with the WAVEWATCH-III (WW3) wave model forced by CCMP wind … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…To investigate the climatic characteristics and long-term trends in the global wave field, reliable and extended time series of data are required. Almost all previous studies used satellite altimeter data [1,17,19], numerical hindcast outputs [20,21], buoy data [22,23], ship observations [24], and/or reanalysis data [25][26][27] to investigate the trend in ocean wave conditions. We used ERA5 [28] and ERA-Interim [29] reanalysis datasets produced by the European Center for Medium-Range Weather Forecast (ECMWF), satellite altimeter data from the French Research Institute for the Exploitation of the Sea (IFREMER), and National Data Buoy Center (NDBC) buoy data to statistically analyze global wave trends [30].…”
Section: Datamentioning
confidence: 99%
“…To investigate the climatic characteristics and long-term trends in the global wave field, reliable and extended time series of data are required. Almost all previous studies used satellite altimeter data [1,17,19], numerical hindcast outputs [20,21], buoy data [22,23], ship observations [24], and/or reanalysis data [25][26][27] to investigate the trend in ocean wave conditions. We used ERA5 [28] and ERA-Interim [29] reanalysis datasets produced by the European Center for Medium-Range Weather Forecast (ECMWF), satellite altimeter data from the French Research Institute for the Exploitation of the Sea (IFREMER), and National Data Buoy Center (NDBC) buoy data to statistically analyze global wave trends [30].…”
Section: Datamentioning
confidence: 99%
“…In addition to the large-scale climate indices, seven welldocumented environmental indices in the YS, including sea surface temperature (SST), sea surface salinity (SSS), sea level pressure (SLP), scalar wind (SW), wind direction (WD), air temperature (AT), and precipitable water content (PWC), were also selected to represent regional environmental conditions (Cui and Zorita, 1998;Park et al, 2015;Zheng et al, 2015) and to test the responses of IFCSs. More details on these environmental indices are provided in Supplementary Table 1.…”
Section: Pressure Variablesmentioning
confidence: 99%
“…In contrary, enhanced heat loss through the increase in latent heat flux is mainly responsible for the negative heat flux anomalies in the warm regime. A study by Zheng et al (2015) revealed that the surface wind speed over the SCS shows a linear increasing trend of 3.38 cm s −1 per year during 1988-2011. However, the linear trend is observed to be almost negligible from 1988 to 1996.…”
Section: Scs Sst Linear Trends and Regime Shiftmentioning
confidence: 99%